2019
DOI: 10.1039/c9sm01055f
|View full text |Cite
|
Sign up to set email alerts
|

Micropattern-controlled wicking enhancement in hierarchical micro/nanostructures

Abstract: Micropattern-controlled two-stage wicking dynamics dictate the enhancement of wicking in hierarchical micro/nanostructured surfaces over bare microstructures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…More recently, the enhancement of the capillary wicking capability has been demonstrated by coupling nanostructures and microstructures on the hierarchical structured surfaces. Hierarchical structures reported recently include nanocactus arrays, 35 micropillars with nanowires, 36 nanorods on micropillars, 37 and nanoporous micropillared surfaces. 38 The hierarchical structures show faster wicking speed compared to single-scaled structures, which is due to the additional capillary pressure by nanostructures and the minimized viscous resistances by microstructures.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the enhancement of the capillary wicking capability has been demonstrated by coupling nanostructures and microstructures on the hierarchical structured surfaces. Hierarchical structures reported recently include nanocactus arrays, 35 micropillars with nanowires, 36 nanorods on micropillars, 37 and nanoporous micropillared surfaces. 38 The hierarchical structures show faster wicking speed compared to single-scaled structures, which is due to the additional capillary pressure by nanostructures and the minimized viscous resistances by microstructures.…”
Section: Introductionmentioning
confidence: 99%
“…This typical example can be considered as a base line for studying capillary flow in micro/nano structured surface in association with phase change heat transfer enhancement. Similar concept for studying the magnitude of liquid spread/rise has been applied and proved experimentally and computationally by various researchers [15][16][17][18][19][20][21][22][23] which is elaborated in Table I.…”
Section: A Role Of Micro/nano Structures In Chf Enhancementmentioning
confidence: 98%
“…They observed that the wetting of this particle induced the formation of a meniscus at its base and the high capillary pressure (∼curvature) of this meniscus locally accelerated contact line motion by a factor of 100 . Increased liquid propagation speeds have also been observed for both regular textures and hierarchical multiscale textures. , Interestingly, the local acceleration and deceleration on textured substrates yield a z ∼ t 1/2 ( t , time) scaling with macroscopic propagation distance ( z ). In contrast, the spreading distance on a flat, smooth surface is known to follow Tanner’s law, z ∼ t 1/10 .…”
Section: Introductionmentioning
confidence: 98%
“…6 Increased liquid propagation speeds have also been observed for both regular textures 5 and hierarchical multiscale textures. 8,9 Interestingly, the local acceleration and deceleration on textured substrates yield a z ∼ t 1/2 (t, time) scaling with macroscopic propagation distance (z). In contrast, the spreading distance on a flat, smooth surface is known to follow Tanner's law, z ∼ t 1/10 .…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation